Detection of formate, rather than carbon monoxide, as the stoichiometric co-product in conversion of fatty aldehydes to alkanes by a cyanobacterial aldehyde decarbonylase - Warui, Douglas M. (2011)
The second of two reactions in a recently discovered pathway through which saturated fatty acids are converted to alkanes (and unsaturated fatty acids to alkenes) in cyanobacteria entails scission of the C1–C2 bond of a fatty aldehyde intermediate by the enzyme aldehyde decarbonylase (AD), a ferritin-like protein with a dinuclear metal cofactor of unknown composition. We tested for and failed to detect carbon monoxide (CO), the proposed C1-derived co-product of alkane synthesis, following the in vitro conversion of octadecanal (R-CHO, where R = n-C(17)H(35)) to heptadecane (R-H) by the Nostoc punctiforme AD isolated following its overproduction in Escherichia coli. Instead, we identified formate (HCO(2)(−)) as the stoichiometric co-product of the reaction. Results of isotope-tracer experiments indicate that the aldehyde hydrogen is retained in the HCO(2)(−) and the hydrogen in the nascent methyl group of the alkane originates, at least in part, from solvent. With these characteristics, the reaction appears to be formally hydrolytic, but the improbability of a hydrolytic mechanism having the primary carbanion as the leaving group, the structural similarity of the ADs to other O(2)-activating non-heme di-iron proteins, and the dependence of in vitro AD activity on the presence of a reducing system implicate some type of redox mechanism. Two possible resolutions to this conundrum are suggested.